TECHNICAL EFFICIENCY OF ORGANIC RICE IN SUMBERNGEPOH VILLAGE, LAWANG SUB DISTRICT, MALANG DISTRICT - Agil Narendar; Nuhfil Hanani; S Syafrial (Socio-Economics/Agribusiness Department, 2021)
Rice plants have a proportion of 6 percent or fifth in the world's classification of organic cereal crops (Research Institute of Organic Agriculture, 2017). The problem in organic rice farming is that production and productivity tend to be lower than those of non-organic rice. In addition to the transition from agriculture to organic farming, the factor of input use also has a big influence. This study aims to analyze the level of technical efficiency and the value of organic rice input. The census sample consisted of 45 organic rice farmers. The data used is data in the 2016-2017 rainy season. The data analysis method uses DEA analysis with the assumption of CRS Input. Based on the results of the analysis, farmers are not yet technically efficient because they have an average technical efficiency value of less than 1, which is 0.879. The number of technically efficient farmers with a TE value of 1 is 13 farmers, while the number of farmers who are inefficient is 32 farmers with a TE value of <1. There are slack values such as seeds 3.15 Kg/Ha, solid organic fertilizer 276.58 Kg/Ha, liquid organic fertilizer 1.07 L/Ha, green manure 505.10 Kg/Ha, vegetable pesticides 1.25 L/Ha, and 6.67 daily workers/ha. In addition, there are projected input values, namely seeds 28.66 Kg/Ha, solid organic fertilizer 2170.30 Kg/Ha, liquid organic fertilizer 10.23 L/Ha, green manure 7048.76 Kg/Ha, vegetable pesticides 9.61 L /Ha, and Labor 185.80 daily workers/Ha. Furthermore, the projected value of this input is a recommendation to farmers so that they can be technically efficient.